Cross-border activities, taxation and the European single market - Eckhardt Bode; Christiane Krieger-Boden; Konrad Lammers (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
In November 1991, the Commission of the European Communities commissioned the Institut für Weltwirtschaft to carry out a report on `Taxation in Border Regions'. This study is a revised version of the report, which was submitted in 1993. The purpose of this study is to analyse the present pattern of cross-border activities, in particular cross-border shopping, cross-border commuting and cross-border movements of enterprises within the EU. Special attention is given to the extent that these activities are induced by differences in taxation between member countries. Furthermore, the study provides answers to the question of how cross-border activities might be affected by the European Single Market. Each cross-border activity is analysed in two border regions: cross-border shopping in the Danish-German border region (Sønderjylland, Südschleswig) and in the Euregio Meuse-Rhine, the border region between Belgium, Germany and the Netherlands; cross-border commuting and cross-border movements of enterprises in the Euregio Meuse-Rhine and in the French-German border region Alsace-Baden.
Keywords: 330; Grenzüberschreitender Verkehr; Konsumentenverhalten; Berufsverkehr; Direktinvestition; Steuerbelastung; Dänemark; Deutschland; Frankreich; Euregio Maas-Rhein